Lessons learned about the application of adaptive testing in several first-year university courses. (22nd June 2022) - Angelone, Anna Maria; Galassi, Alessandra; Vittorini, Pierpaolo
The adoption of computerised adaptive testing (CAT) instead of classical testing (FIT) raises questions from both teachers' and students' perspectives. The scientific literature shows that teachers using CAT instead of FIT should experience shorter times to complete the assessment and obtain more precise evaluations. As for the students, adaptive testing seems to increase their engagement, whereas the impossibility to revise the already given questions is usually seen as a detrimental characteristic. In such a context, the paper reports on a study concerning the aforementioned points. The outcomes seem almost all inline with the literature: no particular usability issues were detected, CAT is faster than FIT, and CAT does not seem more engaging than FIT. All these findings are reported in the conclusions as a list of suggestions to teachers interested in switching from FIT to CAT.